Laser‐ and Ion‐Induced Defect Engineering in WS2 Monolayers. Issue 1 (23rd November 2020) - Asaithambi, Aswin; Kozubek, Roland; Prinz, Günther M.; Reale, Francesco; Pollmann, Erik; Ney, Marcel; Mattevi, Cecilia; Schleberger, Marika; Lorke, Axel
Abstract : Tungsten disulfide is one of the prominent transition metal dichalcogenide materials, which shows a transition from an indirect to a direct bandgap as the layer thickness is reduced down to a monolayer. To use WS 2 monolayers in devices, detailed knowledge about the luminescence properties regarding not only the excitonic but also the defect‐induced contributions is needed. Herein, WS 2 monolayers are irradiated with Xe 30 + ions with different fluences to create different defect densities. Apart from the excitonic contributions, two additional emission bands are observed at low temperatures. These bands can be reduced or even suppressed, if the flakes are exposed to laser light with powers up to 1.5 mW. Increasing the temperature up to room temperature leads to recovery of this emission, so that the luminescence properties can be modified using laser excitation and temperature. The defect bands emerging after ion irradiation are attributed to vacancy defects together with physisorbed adsorbates at different defect sites. Abstract : It is demonstrated that in almost‐defect‐free WS2 monolayers, it is possible to induce defects and defect‐bound emissions in a controlled fashion using Xe 30 + ion irradiation. The results also show that the induced defects and defect‐bound emissions can be further modulated/engineered by laser excitation and temperature cycling. A model to describe the origin of the defect‐bound emissions is given.